Gait and Neuromuscular Changes Are Evident in Some Masters Club Level Runners 24-h After Interval Training Run - Riazati, Sherveen; Caplan, Nick; Matabuena, Marcos; Hayes, Philip R. (Frontiers in Sports and Active Living, 2022)
PURPOSE: To examine the time course of recovery for gait and neuromuscular function immediately after and 24-h post interval training. In addition, this study compared the impact of different statistical approaches on detecting changes. METHODS: Twenty (10F, 10M) healthy, recreational club runners performed a high intensity interval training (HIIT) session consisting of six repetitions of 800 meters. A 6-minute medium intensity run was performed pre, post, and 24-h post HIIT to assess hip and knee kinematics and coordination variability. Voluntary activation and twitch force of the quadriceps, along with maximum isometric force were examined pre, post, and 24-h post HIIT. The time course of changes were examined using two different statistical approaches: traditional null hypothesis tests and ‘real’ changes using minimum detectable change. RESULTS: Immediately following the run, there were significant (P < 0.05) increases in hip frontal kinematics and coordination variability. The runners also experienced loss of muscular strength and neuromuscular function immediately post HIIT (P < 0.05). Individual assessment, however, showed that not all runners experienced fatigue effects immediately post HIIT. Null hypothesis significance testing revealed a lack of recovery in hip frontal kinematics, coordination variability, muscle strength and neuromuscular function at 24-h post, however the use of minimum detectable change suggested that most runners had recovered. CONCLUSION: High intensity interval training caused immediate altered running kinematics along with central and peripheral decrements in neuromuscular function. Most runners had recovered within 24-hours, although a minority still exhibited signs of fatigue. The runners that were not able to recover prior to their run at 24-hr were identified to be at an increased risk of running-related injury.